The influence of blood volume changes on leucocyte and lymphocyte subpopulations in elite swimmers following interval training of varying intensities - Kargotich, S.; Keast, D.; Goodman, C.; Crawford, G. P.; Morton, A. R. (International Journal of Sports Medicine, 1997)
The effect that exercise induced blood volume (BV) changes may have on the concentrations of leucocyte and lymphocyte subpopulations following exercise is controversial. Eight nationally ranked swimmers undertook 15 x 100 m swimming intervals (ITS) at 70% and 95% of maximal exercise intensity separated by 2 min recovery periods. Venous blood samples were collected prior to exercise (PRE), immediately post exercise (POST) and at 30, 60, 120 and 150-min post exercise. Control samples were taken on a rest day (R). Only the 95% ITS induced a significant (p < 0.01) reduction in PV (-7.3 +/- 1.1%) and BV (-4.0 +/- 0.6%) POST as calculated according to changes in haemoglobin and haematocrit. Total leucocyte and subset numbers (neutrophils, lymphocytes, monocytes), with the exception of eosinophils, increased significantly (p < 0.01) POST following the 95% ITS, and total leucocyte and neutrophils remained elevated (30% and 114% respectively) (p < 0.01) while lymphocytes progressively decreased by 36% (p < 0.01) at 150-min after exercise. The 70% ITS elicited a decrease (30%) (p < 0.01) only in lymphocyte cell numbers at 60 and 120-min post exercise. The 95% ITS induced significant increases (p < 0.01) in most lymphocyte cell subsets [CD19+ (27%); CD16+ (525%); CD16+ CD25+ (58%); CD4+ (48%); CD8+ (65%)] POST, with a significant reduction (32%) (p < 0.01) in the CD4+:CD8+ lymphocyte ratio. Numbers of CD19+; CD16+; CD5+; CD4+ and CD8+ lymphocytes, while not significantly changed POST following the 70% ITS, were significantly depressed (p < 0.01) during the recovery period. No significant changes were seen in leucocyte or lymphocyte subset numbers during R. All measured leucocyte and lymphocyte subset cell numbers at each ITS were corrected for changes in BV, and there were no significant differences between measured or BV corrected values for any of the cell populations at either of the ITS. Results suggest that while high intensity swimming exercise stress caused significant changes in the numbers and proportions of leucocytes, lymphocytes and their sub-classes, BV changes did not contribute significantly to the changes which occurred. The cell changes therefore, were truly representative of cell movements into and out of the peripheral blood circulation.